Iris, la mensajera de los dioses. (Estudio iconográfico de sus representaciones en el arte griego) - María Isabel Rodríguez López (Anales de Historia del Arte, 2004)
The Rainbow was personified in Poetry and Greek Art as a winged, young and fast woman called Iris, who was in charged on transmiting the messages of Olimpic Gods, which she was watchful servant. The content of this work is focused on iconographical depictings of this deity in Greek Art, based on different literary sources. Not only the mythological profile of the Godess but her artistic depictings were originated in Archaic Period, but her iconographical atributes, her functions and her images have experienced many changes in the future historicaly but also stylistic as part as the Greek World, and was converted in iconographical prototipes for Western Art.